Laterite Sampling Preparation for Gold Exploration Survey at Western Burkina Faso, Northern Extension of the Lawra Belt - Arhin, Emmanuel; Zango, Musah S; Ruerrger, Rene K (International Journal of Geography and Geology, 2014)
Laterite samples were divided into three and each sample was prepared differently for Au analysis using FA-AAS. The sample-type was identified based on the preparation end-material. The laterite sub sample types were field sample-sieved, field sample crushed and raw field sample-unprocessed. The Au analysis on these sub-samples showed 67% of the field sieved samples from the entire laterite samples had significant Au assays, 25% for the crushed field samples, 8% of both sieved and crushed samples had equal Au geochemical levels from KSG 009 samples. The raw field samples unprocessed returned insignificant Au assays. The study found field sieved samples of < 125 um size fraction to be the best sample preparation method for laterite samples and conclude that it should be employed to detect concealed Au mineralization in laterite capping terrains in the savannah regions.